Les Archives de la planète, entre ressource documentaire et matière à récits - Valérie Perlès (Ateliers d'Anthropologie)
The technical developments of the late 19th century, which favoured travel and the mechanical recording of reality, gave rise to world-documentation ventures. Banker, philanthropist and pacifist Albert Khan created The Archives of the Planet, one of the richest collections of colour images and films between 1909 and 1931. During Albert Khan’s lifetime, the academic, documentary, activist and aesthetic dimensions interacted. Since then, the collections have been passed on to the department of Hauts-de-Seine, and the banker’s estate has become a museum. This article shows to what extent the heterogeneous character of the initial aims are found in current uses of the archives, between a simple documentary reservoir on the world at that time, a scientific contextualisation project, and appropriations by memory and art.